Insight into the mechanism of tetrachlorobisphenol A (TCBPA)-induced proliferation of breast cancer cells by GPER-mediated signaling pathways. (15th April 2021) - Lei, Bingli; Tang, Qianqian; Sun, Su; Zhang, Xiaolan; Huang, Yaoyao; Xu, Lanbing
Abstract: Tetrachlorobisphenol A (TCBPA), a chlorinated derivative of bisphenol A, is an endocrine disruptor based on interaction with nuclear estrogen receptor alpha (ERα). However, there is only limited data on the mechanisms through which TCBPA-associated estrogenic activity is related to the membrane G protein-coupled estrogen receptor (GPER) pathway. In this study, three human breast cancer cell lines-MCF-7, SKBR3, and MDA-MB-231 cells were used to evaluate whether, as well as how, TCBPA at concentration range of 0.001–50 μM affect cell proliferation. The role of GPER signaling in TCBPA-induced cell proliferation was studied by analyzing the protein expression and mRNA levels of relevant signal targets. The results showed that low concentrations of TCBPA significantly induced the proliferation of MCF-7, SKBR3, and MDA-MB-231 cells, with MCF-7 cells being the most sensitive to TCBPA exposure. Low-concentration TCBPA also upregulated the expression of GPER, CyclinD1, c-Myc, and c-Fos proteins, as well as increased the phosphorylation of extracellular signal-regulated-kinase 1/2 (Erk1/2) and protein kinase B (Akt). Additionally, the mRNA levels of genes associated with estrogen signaling pathways also increased upon exposure to TCBPA. However, the phosphorylation of Erk1/2 and Akt decreased when the cells were treated with GPER inhibitor G15 and phosphatidylinositide 3-kinase (PI3K) inhibitor wortmannin (WM) prior to TCBPA exposure. Besides, the increased proliferation of breast cancer cells induced by TCBPA were also inhibited. In ERα-positive MCF-7 cells, TCBPA also upregulated ERα expression, and ERα was found to interact with GPER-mediated signaling. The results indicate that GPER activates the PI3K/Akt and Erk1/2 signal cascades to drive the cell proliferation observed for low concentrations of TCBPA. The presented results suggest a new mechanism by which TCBPA exerts estrogenic action in breast cancer cells, namely, GPER signaling in an ERα-independent manner, and also highlights the potential risks to human health of the usage of TCBPA. Graphical abstract: Image 1 Highlights: TCBPA-induced estrogenic activity through the GPER pathway was evaluated. Low concentration TCBPA induced the proliferation of breast cancer cells. TCBPA can activate the Erk1/2 and PI3K/Akt pathways via GPER. GPER plays a key role in TCBPA-induced proliferation of breast cancer cells. Crosstalk between the ERα and GPER pathways exists in ERα-positive cells. Abstract : A new mechanism for TCBPA-associated estrogenic action based on GPER-mediated signaling was evaluated in breast cancer cells.